(untitled) (KULT_online, 2021)
In her doctoral thesis on media theory, Karin Janker analyzes the dual influence of literature and the early cinema of the 20th century with the naive notion of a medium that wants to make itself indistinguishable from reality. For this purpose, she draws on six contemporaneous novels that influenced the development of cinema as prefiguratives. The connection to virtual realities, fowhose potentials and risks she makes visible, provides a current reference.